PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) DENGAN AUTHENTIC ASSESSMENT UNTUK MENINGKATKAN HASIL DAN AKTIVITAS BELAJAR PADA MATERI LUAS PERMUKAAN PRISMA DAN LIMAS SISWA KELAS VIII SMP NEGERI 1 JEMBER SEMESTER GENAP TAHUN AJARAN 2012 - Yuniar, Devi; Hobri, H; Sugiarti, Titik (Kadikma, 2013)
Abstract. In mathematics learning, the scoring method used was still dominated by one scoring method which only measure the students’ factual knowledge. Thus, the scoring method should be integrated in the teaching learning process, not merely on the result of learning it self. This research was conducted to improve the grade VIII-I student’s learning achievement and their active participation through the implication of Team Games Tournament (TGT) method of cooperative learning type with authentic assessment on the surface area of the prism and pyramid at SMPN 1 Jember in the 2012/2013 academic year. The research design was Classroom Action Research (CAR), and the data collecting method used was observation, test, interview, and documentation. From the actions implemented in each cycle, it was proved that the students’ score improved from 74,68% in Cycle 1, to 80,76% in Cycle 2. Thus, the average percentage of the second cycle was 76,32% and it fulfilled the research criteria, it showed that the implication of TGT can improve the students’ learning achievment and their active participation. Key Words : TGT, authentic assessment, surface area of the prism and pyramid